A CASE WITH VERTEBRAL HYDATID DISEASE SHOWING MULTIPLE RELAPSES - A. Salim Göktepe; Ayşe Sarsan; Bilge Yılmaz; Rıdvan Alaca; Ünsal Coşkun (Archives of Rheumatology, 2004)
Vertebral hydatid disease is relatively common in our country while it is very rare in western countries. It may lead to serious complications; besides its morbidity, it is reported to have 14-58% of mortality rate. Paraple-gia or spinal root compression may occur in 25-84% of the patients. Surgical excision of the cyst is reported to be the treatment of choice. However, the rate of relapse is known to be high. In this article, a case with vertebral hydatid disease having paraplegia and experiencing relapses after several operations is being reported.